Data for "Beyond Magic Numbers: Atomic Scale Equilibrium Nanoparticle Shapes for Any Size" - Rahm, J. Magnus; Erhart, Paul (Chalmers University of Technology, 2023)
This record contains ASE databases in sqlite format that contain the minimum energy structures of nanoparticles of Ag, Au, Cu, and Pd as determined in the paper "Beyond Magic Numbers: Atomic Scale Equilibrium Nanoparticle Shapes for Any Size", Rahm and Erhart, Nano Letters 17, 5775 (2017); doi: 10.1021/acs.nanolett.7b02761

The access-database.py script included in this record demonstrates how to access the databases. It requires the ASE package to be installed.
Keywords: Nanoparticles; Wulff construction; Atomic scale simulations; Physical Sciences; Fysik